Moisture but not temperature manipulations influence abundance of the free-living larvae of a parasitic nematode infecting Svalbard reindeer - T. M. Moerman; R. Wetherbee; M. Renčo; A. Stien; S. J. Coulson; L. E. Loe (Polar Biology, 2026)
Climate in the Arctic is changing and this may influence parasite-host interactions. Infective free-living larvae of gastrointestinal parasitic nematodes (GIN) are sensitive to environmental conditions. Climate change is thus expected to impact the transmission of these parasites. The encounter between infective larvae and grazing herbivores is likely to depend on vertical distribution of the larvae in soil and vegetation. However, research on the combined effects of temperature and moisture on vertical distribution of GIN larvae is limited. In this full factorial replicated field experiment on Svalbard, we studied the vertical distribution of Ostertagia gruehneri, an important GIN that infects Svalbard reindeer. Larvae were added to experimental plots on the field site and exposed to different temperature and watering conditions. We then tested the prediction that exposure to warmer and drier conditions would result in O. gruehneri larvae moving into the soil, while exposure to cooler and wetter conditions would result in the larvae moving into the vegetation. Five days after the introduction of larvae, we found, as expected, a lower larval abundance in the vegetation under the drier than wetter watering conditions. However, larval abundance in soil was similar under the different watering conditions. We propose larval mortality in the vegetation under the drier water regime as the most probable mechanism explaining these results. Contrary to our expectations, our manipulated temperature increases did not affect abundance in the soil or in vegetation. These results have important implications for understanding parasite availability and transmission into Svalbard reindeer in a changing Arctic.

Pelagic sharks target long‐lived, retentive anticyclonic eddies in the Northwest Atlantic Ocean - Camrin D. Braun; Peter Gaube; Alice Della Penna; Simon R. Thorrold; Laura H. McDonnell; G. Chris Fischer; Gonzalo Mucientes; Nuno Queiroz; Mahmood Shivji; David W. Sims; Gregory B. Skomal; Bradley Wetherbee; et al. (Limnology and Oceanography, 2025)
Open ocean ecosystems represent the largest habitat on Earth and are highly dynamic in time and space. Mesoscale eddies are a primary driver of this variability and serve a key structural role in ocean ecosystems. Eddies modulate marine biodiversity beyond their impacts on plankton, influencing many ecologically and commercially important predators that may preferentially occupy anticyclonic eddies. However, how animal‐eddy interactions scale across predator species and the mechanistic drivers of these relationships remain an area of active research. We integrated satellite tracking data for sharks with observations of mesoscale eddies to determine how four shark species interact with eddies in the Gulf Stream region. Based on over 24,000 tracking days, we found that blue, white, and shortfin mako sharks selected for the cores of anticyclones while the use of eddies by tiger sharks was less conspicuous. Some particularly large and long‐lived anticyclones were occupied by tagged sharks for multiple weeks suggesting that these eddies may serve as hotspots for pelagic predators.

Plant Responses to Anomalous Heat and Drought Events in the Sonoran Desert - Benjamin T. Wilder; Kevin R. Hultine; Wetherbee Bryan Dorshow; Sula E. Vanderplank; Blanca R. López; Alfonso Medel‐Narváez; Monica Marvan; Kristen Kindl; Aryn Musgrave; Shane Macfarlan; Exequiel Ezcurra (Global Change Biology, 2025)
A shift to greater aridification in dry regions of the world is ongoing and rapidly increasing in intensity, including in the biodiverse Sonoran Desert of the Southwest United States and northern Mexico. In addition to experiencing over two decades of drought, the Sonoran Desert is facing anomalous heat events that are increasing in frequency, evidenced in a record hot and dry period from 2020 to 2021. This article evaluates the impacts of the 2020–2021 region‐wide heat and drought event at three scales: (1) a landscape level assessment of ecosystem stress across the entirety of the Sonoran Desert based on precipitation and temperature data from meteorological stations and a satellite‐derived vegetation health index (VHI), (2) assessments of stress on iconic columnar cacti and succulent trees, and (3) mechanistic plant responses to extreme heat and drought, and secondary biotic stressors from insect attacks. 2020 was the hottest and driest year since 1980 across the Sonoran Desert region, and vegetation health, determined from VHI, was also near its lowest point. Field‐based assessments of columnar cacti across the Sonoran Desert revealed high levels of acute plant stress, including cactus scorching, defined by rapid onset of discolored photosynthetic tissue that leads to permanent photosynthetic dysfunction and increased plant mortality. Tissue scorching corresponded with a three‐fold increase in mortality of giant cactus species across the region relative to background levels following 2020–2021. Likewise, repeated plant health surveys show a persistent legacy of the 2020–2021 anomaly, resulting in a marked reduction in the current health and survival of the iconic giant saguaro ( Carnegiea gigantea ) in the northern Sonoran Desert. This multi‐scale assessment of previously anomalous heat and drought events on succulent desert plants shows landscape‐wide impacts that could fundamentally reshape populations of these keystone species and the communities that depend on them.

Initial comparison of pollen counting methods using precipitation and ambient air samples and automated artificial intelligence to support national monitoring objectives - Gregory A. Wetherbee; David A. Gay; Eric R. Uram; Terri L. Williams; Andrew P. Johnson (Aerobiologia, 2023)

First insights into the vertical habitat use of the whitespotted eagle ray Aetobatus narinari revealed by pop‐up satellite archival tags - Lauran R. Brewster; Brianna V. Cahill; Miranda N. Burton; Cassady Dougan; Jeffrey S. Herr; Laura Issac Norton; Samantha A. McGuire; Marisa Pico; Elizabeth Urban‐Gedamke; Kim Bassos‐Hull; John P. Tyminski; Robert E. Hueter; et al. (Journal of Fish Biology, 2021)
The whitespotted eagle ray Aetobatus narinari is a tropical to warm‐temperate benthopelagic batoid that ranges widely throughout the western Atlantic Ocean. Despite conservation concerns for the species, its vertical habitat use and diving behaviour remain unknown. Patterns and drivers in the depth distribution of A. narinari were investigated at two separate locations, the western North Atlantic (Islands of Bermuda) and the eastern Gulf of Mexico (Sarasota, Florida, U.S.A.). Between 2010 and 2014, seven pop‐up satellite archival tags were attached to A. narinari using three methods: a through‐tail suture, an external tail‐band and through‐wing attachment. Retention time ranged from 0 to 180 days, with tags attached via the through‐tail method retained longest. Tagged rays spent the majority of time (82.85 ± 12.17% S.D.) within the upper 10 m of the water column and, with one exception, no rays travelled deeper than ~26 m. One Bermuda ray recorded a maximum depth of 50.5 m, suggesting that these animals make excursions off the fore‐reef slope of the Bermuda Platform. Individuals occupied deeper depths (7.42 ± 3.99 m S.D.) during the day versus night (4.90 ± 2.89 m S.D.), which may be explained by foraging and/or predator avoidance. Each individual experienced a significant difference in depth and temperature distributions over the diel cycle. There was evidence that mean hourly depth was best described by location and individual variation using a generalized additive mixed model approach. This is the first study to compare depth distributions of A. narinari from different locations and describe the thermal habitat for this species. Our study highlights the importance of region in describing A. narinari depth use, which may be relevant when developing management plans, whilst demonstrating that diel patterns appear to hold across individuals.

Global population genetic dynamics of a highly migratory, apex predator shark - Andrea M. Bernard; Kevin A. Feldheim; Michael R. Heithaus; Sabine P. Wintner; Bradley M. Wetherbee; Mahmood S. Shivji (Molecular Ecology, 2016)
Knowledge of genetic connectivity dynamics in the world's large‐bodied, highly migratory, apex predator sharks across their global ranges is limited. One such species, the tiger shark ( Galeocerdo cuvier ), occurs worldwide in warm temperate and tropical waters, uses remarkably diverse habitats (nearshore to pelagic) and possesses a generalist diet that can structure marine ecosystems through top‐down processes. We investigated the phylogeography and the global population structure of this exploited, phylogenetically enigmatic shark by using 10 nuclear microsatellites ( n = 380) and sequences from the mitochondrial control region ( CR , n = 340) and cytochrome oxidase I gene ( n = 100). All three marker classes showed the genetic differentiation between tiger sharks from the western Atlantic and Indo‐Pacific ocean basins (microsatellite F ST > 0.129; CR Φ ST > 0.497), the presence of North vs. southwestern Atlantic differentiation and the isolation of tiger sharks sampled from Hawaii from other surveyed locations. Furthermore, mitochondrial DNA revealed high levels of intraocean basin matrilineal population structure, suggesting female philopatry and sex‐biased gene flow. Coalescent‐ and genetic distance‐based estimates of divergence from CR sequences were largely congruent ( d corr = 0.0015–0.0050), indicating a separation of Indo‐Pacific and western Atlantic tiger sharks

Development of the primary bacterial microfouling layer on antifouling and fouling release coatings in temperate and tropical environments in Eastern Australia - Paul J. Molino; Samantha Childs; Maeve R. Eason Hubbard; Janet M. Carey; Mark A. Burgman; Richard Wetherbee (Biofouling, 2009)

Early growth and juvenile population structure of lemon sharks Negaprion brevirostris in the Atol das Rocas Biological Reserve, off north‐east Brazil - R. H. A. Freitas; R. S. Rosa; S. H. Gruber; B. M. Wetherbee (Journal of Fish Biology, 2006)
Lemon sharks Negaprion brevirostris were sampled in the Atol das Rocas, a nursery area, on nine occasions from March 1999 to October 2003, during which 157 individuals were tagged and 35 were recaptured. The male : female sex ratio of captured individuals was 1 : 1·12. Mean ± s . d . growth rates were 24·7 ± 3·4 cm year −1 in total length ( L T ), 20·7 ± 3·2 cm year −1 in fork length, and 19·5 ± 2·7 cm year −1 in precaudal length. There was no significant difference in growth rates between males and females. Mean ± s . d . increase in mass was 2565 ± 762 g year −1 . The von Bertalanffy growth parameters estimated by the Fabens method based on L T were: k = 0·077, L ∞ = 399·9 cm and t 0 = −2·16. Despite the large variation of environmental conditions, particularly of tidal range and currents, and the lack of protective mangrove cover in the nursery area at Atol das Rocas, juvenile lemon sharks grew relatively faster than at other nurseries. Such rapid growth could be a response to abundant food availability or high risk of predation by adults that enter the nursery area.

The application of atomic force microscopy to topographical studies and force measurements on the secreted adhesive of the green alga Enteromorpha - J. A. Callow; S. A. Crawford; M. J. Higgins; P. Mulvaney; R. Wetherbee (Planta, 2000)

Subcellular location and composition of the wall and secreted extracellular sulphated polysaccharides/proteoglycans of the diatomStauroneis amphioxys Gregory - M. J. McConville; R. Wetherbee; A. Bacic (Protoplasma, 1999)

A new technique for preparing biominerals for atomic-force microscopy - L. M. Egerton-Warburton; S. T. Huntington; P. Mulvaney; B. J. Griffin; R. Wetherbee (Protoplasma, 1998)

The surface periplast component of the protistKomma caudata (Cryptophyceae) self-assembles from a secreted high-molecular-mass polypeptide - L. Perasso; M. Ludwig; R. Wetherbee (Protoplasma, 1997)